Wind Tunnel Tests of UiTM Blended Wing Body - Unmanned Aerial Vehicle (BWB-UAV) Prototype / Wirachman Wisnoe ...[et al.] - Wirachman, Wisnoe; M. Nasir, Rizal E.; Saarani, Wan Aizad Mu; Mohd Saad, Nornashiha; Afiq Mamud, Mohd Amirul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In 2014 Universiti Teknologi MARA (UiTM) Malaysia has been granted a research project under Prototype Research Grant Scheme from the Ministry of Higher Education Malaysia to build a prototype of Blended Wing Body - Unmanned Aerial Vehicle for aerial surveillance. In this paper the aerodynamic characteristics of the prototype in the longitudinal direction are presented in terms of lift coefficient, drag coefficient, and pitching moment coefficient obtained from wind tunnel tests. The tests are conducted on a ¼ scaled half model aircraft placed in UiTM Low Speed Tunnel at wind speed of 20 m/s, 25 m/s, 30 m/s, 35 m/s and 40 m/s representing Reynolds number in the order of 105. For each wind speed, the angle of attack is varied from -10º to 64º to observe the full capability of the aircraft. Visualisation using thread tufts is also executed to see the flow pattern on the surface of the aircraft at certain angles. The results show that the maximum lift coefficient is around 0.65 at 28º angle of attack, the minimum drag coefficient is below 0.03 at zero angle of attack, and the maximum lift-to-drag ratio is about 20 at 3º angle of attack. The pitching moment curve indicates a static stability with negative slope between -7º to 10º angle of attack. Visualisation shows the flow separation progress on the surface of canard, wing and fuselage.